2005
DOI: 10.1080/09593332608618517
|View full text |Cite
|
Sign up to set email alerts
|

Aged Chlorophenol Contaminated Soil's Integrated Treatment by Ozonation, Soil Washing and Biological Methods

Abstract: Traditionally soils contaminated by organic compounds have been treated by biological methods, but aged contaminated soils usually contain refractory and toxic compounds not any more responsive to biological treatment. By oxidation and soil washing the biodegradability and bioavailability of these otherwise recalcitrant compounds can be enhanced. The aim of the study was to optimize and integrate soil washing, ozonation (+ hydrogen peroxide) and biological treatment for the remediation of old saw mill soil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, degradation kinetic rates observed for the removal of PAH from SW solutions by electro-oxidation using graphite electrodes were in the range 0.02-0.2 h -1 [21,164]. As regards to ozone, it was observed significant removal of PAH and chlorophenols from SW solutions (45-65% removal) only when using high doses (> 500 mg O3 L -1 ) [165,166]. Besides, it was reported that high concentration of surfactant decreases gas-liquid mass transfer for both (semi)-volatile pollutants and ozone, thus reducing the effectiveness of the ozone process [167].…”
Section: -Degradation Processes Iii1 -Biological Processesmentioning
confidence: 98%
“…For example, degradation kinetic rates observed for the removal of PAH from SW solutions by electro-oxidation using graphite electrodes were in the range 0.02-0.2 h -1 [21,164]. As regards to ozone, it was observed significant removal of PAH and chlorophenols from SW solutions (45-65% removal) only when using high doses (> 500 mg O3 L -1 ) [165,166]. Besides, it was reported that high concentration of surfactant decreases gas-liquid mass transfer for both (semi)-volatile pollutants and ozone, thus reducing the effectiveness of the ozone process [167].…”
Section: -Degradation Processes Iii1 -Biological Processesmentioning
confidence: 98%